2009 International Students and Young Scientists Workshop "Photonics and Microsystems" 2009
DOI: 10.1109/stysw.2009.5470313
|View full text |Cite
|
Sign up to set email alerts
|

Methods of selectivity improvements of semiconductor gas sensors

Abstract: In this paper, methods for selectivity improvement of semiconductor gas sensors are presented. The frequently used techniques are: temperature modulation, synthesis of new materials, designing new sensor constructions, adopting filter layers and using of sensors array. A comparison between the different methods has been made. It was concluded that the kind of sensing material and filter layer have a strong influence on the sensor parameters. The analysis has shown that the optimal detection temperature change … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…Au nanoparticle gas sensors for VOC detection [21] nanoparticles increasing the gas sensing active area [22. 23]) or introducing catalytically active additives by bulk doping and surface modification [24].…”
Section: Semiconductor Gas Sensorsmentioning
confidence: 99%
“…Au nanoparticle gas sensors for VOC detection [21] nanoparticles increasing the gas sensing active area [22. 23]) or introducing catalytically active additives by bulk doping and surface modification [24].…”
Section: Semiconductor Gas Sensorsmentioning
confidence: 99%
“…In order to improve sensitivity of the sensor different methods had been used including temperature modulation, synthesis of new sensor materials, designing new sensor constructions, adoption of new filter layers and using of sensor array. Therefore, Grzegorz Halek et al [49] made a comparison on methods of selectivity improvements of semiconductor gas sensors and concluded that the kind of sensing material and filter layer have a strong influence on the sensor parameter.…”
Section: Operation Principle Of One-electrode Semiconductor Gas Sensorsmentioning
confidence: 99%
“…Nanostructures of tungsten trioxide (WO 3 ), tin dioxide (SnO 2 ), and zinc oxide (ZnO) have extensively been considered for NO 2 sensing because of their key attributes such as fast response and sensitive detection, portability, and cost-effectiveness. , Particularly, WO 3 is highly capable of NO 2 sensing owing to its unique selectivity to NO 2 , high catalytic activity, and low cost. , However, its NO 2 -sensing properties are still limited and can be further enhanced by optimizing its structural and chemical properties with effective preparation methods and appropriate catalytic additives. , Among available additives, transition metals including gold (Au), , zinc (Zn), silver (Ag), ruthenium (Ru), platinum (Pt), and lanthanum (La) have been explored to augment gas selectivity and responsivity of WO 3 . Table reports NO 2 -sensing characteristics of nanomaterials based on WO 3 with different additives fabricated by several methods.…”
Section: Introductionmentioning
confidence: 99%